Enseñanza de español con el uso de juegos divertidos: una propuesta didáctica estudiantes del 7º grado de educación básica de la EMEF Bom Jardim/Cametá-PA - PRAZERES, Joelma do Socorro Pompeu dos (2023)
This course completion work aims to propose a discussion about the insertion of playful games in the teaching of Spanish in the 7th year of elementary school, and with that the main objective of this work is to make a proposal on the use of playful games for students, and so, we want to show the importance of learning as much Spanish as possible through playful games. The choice for this theme arose from the concern to show how didactic games can facilitate the students' teaching-learning process in Spanish classes, and in order to have a specific north, we directed the studies to the seventh year of elementary school. The central issue was about the teaching process of students in the seventh year of elementary school. The research methodology took place through bibliographical research with some authors who have already written on the subject, as well as through observations in the classroom, made through the mandatory teaching internships, carried out during the course. The method of analysis was qualitative, so we gathered all the knowledge acquired during the internships, which were carried out at the Bom Jardim school, and combined it with the theory of the researched authors and thus, we built a coherent text, where we joined theory and practice. And with that, it was possible to assemble a quality work with a theoretical basis, which can serve as a reference for other possible works related to this theme.